Some considerations of the 210 Pb constant rate of supply (CRS) dating model - J. A. Sanchez‐Cabeza; I. Ani‐Ragolta; P. Masquè (Limnology and Oceanography, 2000)
One of the most widely used radionuclides in the study of recent sedimentation processes is 210 Pb. Its depth profile in sediments is used as input for various dating models, which provide chronologies, mass fluxes, and sedimentation rates. In this work we revisited the CRS (constant rate of supply) model, widely used for dating sediments through 210 Pb. A more general hypothesis (periodic flux [PF]) was proposed and, although it confirmed the validity of CRS chronology, a detailed analysis of the mass sedimentation formula pointed out an inconsistency of the cited model. A new mass sedimentation formula was proposed and validated with a lake sediment core and four marine sediment cores.

Historical Variations in Lead Fluxes in the Pyrenees (Northeast Spain) from a Dated Lake Sediment Core - L. Camarero; P. Masqué; W. Devos; I. Ani-Ragolta; J. Catalan; H.C. Moor; S. Pla; J.A. Sanchez-Cabeza (Water, Air, & Soil Pollution, 1998)